Experimental investigation of smouldering in biomass - Carvalho, E. R.; Veras, CAG; Carvalho, J. A. (Elsevier B.V., 2002)
The smouldering process of wood logs was studied experimentally in a laboratory facility and in prescribed forest bums. The main goal was to check the parameters that initiate and control the stability of the smouldering process. To do so, sample temperatures at five different locations and concentrations of CO, CO2 and O-2 were measured and discussed. By varying the temperature and air supply of the flow tunnel apparatus, different rates of smoulder propagation were identified. In prescribed bums, the main characteristics of the self-sustained smouldering combustion front in logs of different sizes and species are reported. The average smouldering speed in the field is about one order of magnitude lower than that reported for different materials in laboratory experiments. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: smouldering; biomass combustion; heat transfer; Machaerium anguwtifolium